Greenhouse gas emissions and Europe 2020 strategy - Lazányi, János (Acta Agraria Debreceniensis, 2010)
Common Agricultural Policy has identified three priority areas for action to protect and enhance rural heritage: (i) the preservation and development of natural farming and traditional agricultural landscapes; (ii) water management and sustainable use and (iii) dealing with climate change. Measures of Rural Development Plan in EU countries promote the development of agricultural practices for preserving the environment and safeguarding the countryside. This is achieved by targeting rural development and promoting environmental friendly, sustainable practices, like agri-environment schemes. Farmers are encouraged to continue playing a positive role in the maintenance of the countryside and the environment. Changes in total emission between 1990and 2007 do not show any correlation with the total GHG emission. GHG emission was reduced in Hungary, Slovakia, Lithuania, Czech Republic, Romania, Poland, Estonia and Bulgaria, where GHG efficiency is low.